Health impact of China's Air Pollution Prevention and Control Action Plan: an analysis of national air quality monitoring and mortality data - Huang, Jing; Pan, Xiaochuan; Guo, Xinbiao; Li, Guoxing (The Lancet. Planetary health, 2018)
To mitigate the serious levels of air pollution in China, the State Council of China issued the Air Pollution Prevention and Control Action Plan (APPCAP) in 2013. This policy is a milestone in air quality control in China. We aimed to evaluate the effects of the APPCAP on long-term air quality management and the related health impacts in China. We did an analysis of national air quality monitoring and mortality data to estimate the health impact of the APPCAP from 2013 to 2017 in 74 key cities in China. Changes in mortality and in years of life lost (YLL), an indicator that considers life expectancy at death, were calculated to assess the health impact of air quality management during the 5-year period. Between 2013 and 2017, annual average concentrations of PM2·5 decreased by 33·3% (95% CI 16·3–50·3), PM10 by 27·8% (8·0–47·5), sulphur dioxide by 54·1% (28·2–80·0), and carbon monoxide by 28·2% (3·1–53·3) in the 74 key cities. However, no significant change was seen in annual average concentrations of nitrogen dioxide (9·7% reduction; 95% CI −23·0 to 42·4) or ozone (20·4% increase; −30·1 to 71·0). In 2017, as a result of substantial improvements in air quality, there were 47 240 (95% CI 25 870–69 990) fewer deaths and 710 020 (420 230–1 025 460) fewer YLL in the 74 key cities in China than in 2013. Substantial reductions in mortality and YLL related to control of ambient air pollution were achieved from 2013 to 2017 in China, indicating appreciable effectiveness of China's APPCAP. However, emissions control efforts for ozone and nitrogen dioxide should be strengthened in the future. National Natural Science Foundation of China and the National Key Research and Development Program of China.